Wear-resistant and high-temperature-resistant composite polypropylene material for automobile decoration and preparation method thereof

By modifying the carbon-carbon double bond on the surface of the modified carbon sphere and combining with the benzotriazole structure with ultraviolet resistance and combining with a modified flame retardant nucleating agent, composite polypropylene material with significant UV resistance, high temperature resistance and mechanical strength properties was prepared, which solved the problem of insufficient wear resistance and flame retardancy of existing materials.

CN119505470APending Publication Date: 2025-02-25XIANGSHAN ZHUOSHENG AUTO PARTS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411929675.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The wear resistance and flame retardant properties of existing composite polypropylene materials for automotive decoration have not yet reached a satisfactory level, resulting in a reduced structural stability of the material and a reduced filler dispersion, which in turn affects the overall performance of the material.

Method used

Modified polypropylene material is used to modify carbon-carbon double bonds on the surface of the modified carbon sphere and coordinate with the benzotriazole structure with ultraviolet resistance. It is used as a polymerization center to participate in the preparation of the modified polypropylene matrix, and at the same time, a modified flame retardant nucleating agent is used to improve the material's ultraviolet resistance, high temperature resistance and mechanical strength properties.

Benefits of technology

It significantly improves the ultraviolet resistance, high temperature and mechanical strength properties of composite polypropylene materials, enhances the flame retardant and high temperature resistance of the material, and improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005209967310000031
    Figure BDA0005209967310000031
  • Figure BDA0005209967310000032
    Figure BDA0005209967310000032
  • Figure BDA0005209967310000041
    Figure BDA0005209967310000041
Patent Text Reader

Abstract

The invention discloses a wear-resistant and high-temperature-resistant composite polypropylene material for automobile decoration and a preparation method thereof, belongs to the technical field of high polymer materials, and aims to solve the technical problem that the wear resistance and flame retardance of a polypropylene material in the prior art need to be further improved. The modified polypropylene material comprises the following raw materials in parts by weight: 80-100 parts of modified polypropylene, 15-20 parts of a flame-retardant nucleating agent, 3-5 parts of an antioxidant, 3-5 parts of a heat stabilizer and 2-5 parts of a light stabilizer, according to the invention, the prepared modified carbon spheres are used as a filling material and also used as a polymerization center to participate in the preparation of a modified polypropylene matrix, the anti-ultraviolet and wear-resistant modified polypropylene material is prepared by selecting monomers, and the flame-retardant cross-linking agent is prepared in the melt extrusion process of the composite polypropylene material, so that the flame-retardant performance of the composite polypropylene material is improved. The composite polypropylene material with beta crystal form arrangement is generated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a wear-resistant and high-temperature-resistant composite polypropylene material for automobile decoration and a preparation method thereof. Background Art

[0002] The development of wear-resistant and flame-retardant composite polypropylene materials for automotive decoration has gone through a process from basic modification to high-performance composite;

[0003] In the early days, ordinary polypropylene was widely used due to its advantages of light weight, low cost and easy processing. However, its wear resistance and flame retardancy were weak, making it difficult to meet the stringent requirements of automotive interiors. Therefore, fillers such as talcum powder and glass fiber were added to enhance its mechanical properties and dimensional stability. At the same time, lubricants and anti-wear agents were added to improve surface wear resistance. The materials at this stage were already suitable for parts such as door panels and dashboards.

[0004] In recent years, nanotechnology and multifunctional composite modification have promoted the improvement of material performance. The combination of nanoparticles and β-nucleating agents not only improves wear resistance, but also improves flame retardant efficiency;

[0005] At present, the development direction focuses on green, environmentally friendly, high-performance composite materials to meet the needs of lightweight automobiles and energy conservation and emission reduction, while ensuring high safety and long service life.

[0006] Prior art CN104212061B discloses a high-strength wear-resistant flame-retardant polypropylene and a preparation method thereof, which consists of 42-55 parts of a polypropylene matrix, 20-29 parts of a modified filler, 1-4 parts of boron nitride, 18-21 parts of an additive, 1-3 parts of a phosphite antioxidant and 2-5 parts of dimethyl silicone oil. The polypropylene matrix, the modified filler, the boron nitride, the additive, the phosphite antioxidant and the dimethyl silicone oil are uniformly mixed by a high-speed mixer, and then the mixture is added to a granulator for granulation. Then, the granules are added to an injection molding machine for sampling to obtain flame-retardant polypropylene. The addition of a variety of inorganic components improves the fluidity of the polymer and inorganic filler system, improves the toughening effect, and does not require the use of a compatibilizer. Moreover, the use of a variety of additives, glass fibers and flame retardants are all halogen-free materials, which has obvious advantages over traditional polypropylene composite materials.

[0007] However, the above patent blends polypropylene material with flame retardants and modified fillers to achieve the purpose of improving the flame retardancy and wear resistance of the material. However, the rigidity, toughness and strength of the flame retardant itself are low. Dispersing it inside the polypropylene material will lead to a decrease in the structural stability of the polypropylene material and a decrease in the wear resistance of the material. In addition, the mass of the modified filler accounts for a large proportion, which will lead to a decrease in the dispersion of the filler in the polypropylene material, thereby causing the filler to agglomerate, further reducing the wear resistance of the material, enhancing the material density and increasing the material's own weight.

[0008] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0009] The purpose of the present invention is to provide a wear-resistant and high-temperature-resistant composite polypropylene material for automobile decoration and a preparation method thereof, so as to solve the technical problem that the wear resistance and flame retardancy of polypropylene materials in the prior art need to be further improved.

[0010] The purpose of the present invention can be achieved through the following technical solutions:

[0011] A wear-resistant and high-temperature-resistant composite polypropylene material for automobile decoration, comprising the following raw materials in parts by weight: 80-100 parts of modified polypropylene, 15-20 parts of flame retardant nucleating agent, 3-5 parts of antioxidant, 3-5 parts of heat stabilizer and 2-5 parts of light stabilizer;

[0012] Wherein, the preparation method of modified polypropylene comprises the following steps:

[0013] A1. Using propylene gas as a modifier, the surface of the modified carbon spheres is modified to prepare a modified polypropylene matrix;

[0014] A2. Add the modified polypropylene matrix, polymer solution and dichlorobenzene into a reactor, raise the temperature of the reactor to 150-160°C, keep warm and stir for 10-15 minutes, add azobisisobutyronitrile into the reactor, keep warm and react for 1-2 hours, and post-treat to obtain modified polypropylene.

[0015] The reaction equation for preparing modified polypropylene is:

[0016]

[0017] Where:

[0018]

[0019] The reaction principle for preparing modified polypropylene is as follows: under high temperature and the catalysis of a free radical initiator, double bonds on the modified polypropylene matrix, 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol and 1-allyl-3,5-di[3-(trimethoxysilyl)propyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione are exercised to generate free radicals, and after continuous polymerization, modified polypropylene is finally prepared.

[0020] Further, in step A1, the surface modification operation includes the following steps:

[0021] B1, placing the modified carbon spheres and azobisisobutyronitrile in a reaction kettle and stirring for 10-15 minutes at room temperature to obtain a prepolymer mixture;

[0022] B2. The prepolymer mixture is placed in a high-pressure reactor, the temperature of the high-pressure reactor is increased to 200-250° C., the pressure is increased to 15-20 MPa, propylene is introduced, and polymerization is carried out at a constant temperature and pressure for 40-60 minutes to obtain a modified polypropylene matrix.

[0023] The reaction equation for preparing the modified polypropylene matrix is:

[0024]

[0025] The reaction principle for preparing the modified polypropylene matrix is ​​as follows: under high temperature and high pressure, propylene gas continuously polymerizes with double bonds on the surface of the modified carbon spheres under the initiation of azobisisobutyronitrile to form organic polymer chain segments, and finally a modified polypropylene matrix is ​​prepared.

[0026] Furthermore, in step B1, the ratio of modified carbon spheres to azobisisobutyronitrile is 8-10 g:1-2 g, and the stirring rate of the reactor is 80-120 rpm; in step B2, the ratio of prepolymer mixture to propylene is 1 g:4-5 g.

[0027] Further, in step A2, the amount ratio of the modified polypropylene matrix, the polymerization liquid, dichlorobenzene and azobisisobutyronitrile is 8-10g:10-15g:40-60mL:1.0-1.2g, the polymerization liquid is prepared by 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol, 1-allyl-3,5-bis[3-(trimethoxysilyl)propyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and dichlorobenzene in a mass ratio of 1-2g:2.4-3.0g:10-15g, and the post-treatment includes: after the reaction is completed, the reaction kettle is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 100-120°C, and distilled under reduced pressure until no liquid is produced to obtain modified polypropylene.

[0028] Furthermore, the preparation method of the modified carbon spheres comprises the following steps:

[0029] C1. Add nano iron oxide particles, pyrrole and deionized water into a reactor, stir at room temperature for 10-15 minutes, then drop the catalyst into the reactor, continue stirring for 4-6 hours, and perform post-treatment to obtain carbon-encapsulated iron oxide;

[0030] C2, adding carbon-coated iron oxide and 98.0wt% sulfuric acid to a reactor at a temperature of 0-3°C and stirring, keeping the temperature and stirring for 10-15min, adding sodium chlorate to the reactor, keeping the temperature of the reactor at 0-5°C and reacting for 2-4h, adjusting the pH of the reaction system to 7 with a saturated sodium hydroxide solution, and post-treating to obtain hollow carbon spheres;

[0031] C3. Add hollow carbon spheres, 3-(methacryloyloxy)propyltrimethoxysilane, sodium hydroxide and deionized water into a reactor, increase the temperature of the reactor to 30-50°C, keep the temperature for 3-5h, and post-treat to obtain modified carbon spheres.

[0032] The reaction equation for preparing modified carbon spheres is:

[0033]

[0034] The reaction principle for preparing modified carbon spheres is as follows: a large number of hydroxyl groups on the oxidized carbon structure react with the silanol structure produced by the hydrolysis of 3-(methacryloyloxy)propyltrimethoxysilane under alkaline conditions, dehydrate to form a spatial network structure, and finally introduce a double bond structure into the carbon structure to finally prepare modified carbon spheres.

[0035] Furthermore, in step C1, the stirring rate of the reactor is 80-120rpm, the dosage ratio of nano-iron oxide particles, pyrrole, deionized water and catalyst liquid is 2-4g:1-3mL:30-40mL:10-15mL, the catalyst liquid is prepared by ammonium persulfate and deionized water at a dosage ratio of 40-50mg:1-1.2mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the material is transferred to a drying oven at a temperature of 80°C and vacuum dried until the material has a constant weight, and then the material is transferred to a tubular furnace, after nitrogen protection is introduced, the temperature is increased to 600-800°C at a heating rate of 3-5°C / min, and constant temperature calcined for 4-6h to obtain carbon-encapsulated iron oxide.

[0036] Further, in step C2, the stirring rate of the reactor is 80-120 rpm, the amount ratio of carbon-coated iron oxide, 98.0wt% sulfuric acid and sodium chlorate is 5-8g:30-40g:3-5g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and after washing with anhydrous ethanol and deionized water for 3-5 times, the material is transferred to a drying oven at a temperature of 60°C and vacuum dried until the material is constant weight to obtain hollow carbon spheres; In step C3, the dosage ratio of hollow carbon spheres, 3-(methacryloyloxy)propyltrimethoxysilane, sodium hydroxide and deionized water is 8-10g:2-3g:0.8-1g:30-50mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and after washing 3-5 times with anhydrous ethanol and deionized water, the material is transferred to a drying oven at a temperature of 60°C and vacuum dried until the material is constant weight to obtain modified carbon spheres.

[0037] Furthermore, the preparation method of the flame retardant nucleating agent comprises the following steps:

[0038] D1. Deionized water and ethanol are added to a reactor, the temperature of the reactor is raised to 40-50°C, and after being stirred for 10-15 minutes, ammonium polyphosphate, nonylphenol polyoxyethylene ether and 15-20wt% ammonia water are added to the reactor, and after being stirred for 20-30 minutes, triethyl orthosilicate is added dropwise to the reactor, and the mixture is stirred for 2-3 hours, and a flame retardant is obtained by post-processing;

[0039] D2, adding flame retardant, 2,2'-methylene-bis(4,6-di-tert-butylphenyl phosphate) basic aluminum, sodium hydroxide and N,N-dimethylformamide into a reactor, raising the temperature of the reactor to 120-130°C, keeping the temperature for reaction for 30-40 minutes, and post-treating to obtain a modified nucleating agent;

[0040] The reaction equation for preparing the modified nucleating agent is:

[0041]

[0042] In the formula

[0043] The reaction of preparing the modified nucleating agent is as follows: under alkaline organic components and high temperature catalysis, the aluminum hydroxyl groups on 2,2'-methylene-bis(4,6-di-tert-butylphenyl phosphate) basic aluminum and the hydroxyl groups on the flame retardant undergo a dehydration reaction, and a cross-linked structure is obtained after removing the water molecules. The organic solvent significantly enhances the hydrolysis and self-polymerization reaction of 2,2'-methylene-bis(4,6-di-tert-butylphenyl phosphate) basic aluminum, and finally makes it stably cross-linked on the surface of the flame retardant. By limiting the reaction conditions, part of the hydroxyl groups of the flame retardant are retained, and finally the modified nucleating agent is prepared.

[0044] D3. Add modified nucleating agent, 1,3-bis(oxiranylmethyl)-5-(2-propylene)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, saturated sodium hydroxide solution and N,N-dimethylformamide into the reactor, increase the temperature of the reactor to 40-60°C, keep the reaction warm for 20-30 minutes, and post-treat to obtain the flame retardant nucleating agent.

[0045] The reaction equation for preparing the flame retardant nucleating agent is:

[0046]

[0047] Where:

[0048] The reaction principle for preparing the flame retardant nucleating agent is as follows: under alkaline and heating conditions, the epoxy group on 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione opens to generate free radicals, which react with the residual hydroxyl groups on the modified nucleating agent to finally prepare the flame retardant nucleating agent.

[0049] Furthermore, in step D1, the stirring rate of the reactor is 100-120rpm, the amount ratio of deionized water, ethanol, ammonium polyphosphate, nonylphenol polyoxyethylene ether, 15-20wt% ammonia water and triethyl orthosilicate is 20-25mL:6-9mL:4-6g:0.1-0.3g:15-20mL:10-12g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and after washing 3-5 times with anhydrous ethanol and deionized water, the material is transferred to a drying oven at a temperature of 60°C and vacuum dried until the material has a constant weight to obtain a flame retardant.

[0050] Furthermore, in step D2, the amount ratio of flame retardant, 2,2'-methylene-bis(4,6-di-tert-butylphenyl phosphate) basic aluminum, sodium hydroxide and N,N-dimethylformamide is 3-5g:0.8-1.2g:0.3-0.5g:20-30mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and after washing with anhydrous ethanol and deionized water for 3-5 times, the material is transferred to a drying oven at a temperature of 60°C and vacuum dried until the material is constant weight to obtain a modified nucleating agent.

[0051] Furthermore, in step D3, the amount ratio of the modified nucleating agent, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, saturated sodium hydroxide solution and N,N-dimethylformamide is 3-5g:0.3-0.5g:0.3-0.5mL:20-30mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and after washing with anhydrous ethanol and deionized water for 3-5 times, the material is transferred to a drying oven at a temperature of 60°C and vacuum dried until the material has a constant weight to obtain a flame retardant nucleating agent.

[0052] The present invention also provides a method for preparing a wear-resistant and high-temperature resistant composite polypropylene material for automobile decoration, which comprises uniformly mixing modified polypropylene, flame retardant nucleating agent, antioxidant, heat stabilizer and light stabilizer, adding the mixture into a twin-screw extruder, and melt-extruding to obtain composite polypropylene.

[0053] The reaction principle for preparing composite polypropylene is as follows: during high-temperature melt extrusion, the modified polypropylene chain segments undergo partial pyrolysis and polymerize with the double bonds on the surface of the flame retardant nucleating agent to form a stable cross-linked structure, and a large amount of nucleating agents on the surface of the flame retardant nucleating agent promote heterogeneous nucleation of the modified polypropylene to form a β-crystal, and finally composite polypropylene is prepared.

[0054] Furthermore, the antioxidant is one or more of antioxidant 1010, triphenyl phosphite and dilauryl sulfide, the heat stabilizer is one or more of dibutyltin dilaurate, triphenyl phosphate and epoxy soybean oil, and the light stabilizer is one or two of 2-hydroxy-4-octyloxybenzophenone and bis(2,2,6,6-tetramethylpiperidinyl)sebacate; the temperatures of the seven temperature zones of the twin-screw extruder from the feed port toward the discharge port are 200°C, 200°C, 205°C, 215°C, 215°C, 220°C, and 220°C, respectively, the main engine speed of the twin-screw extruder is 80-120rpm, and the pressure is 100-150bar.

[0055] The present invention has the following beneficial effects:

[0056] 1. The present invention prepares modified carbon balls as filling materials and modifies carbon-carbon double bonds on their surfaces to participate in the preparation of modified polypropylene matrix as polymerization centers. The benzotriazole structure and hindered phenol structure with unique UV resistance are selected to coordinate with the hollow modified carbon balls to improve the UV resistance and high temperature resistance of the material and to improve the compatibility of the polypropylene chain segments with the modified carbon balls and the flame retardant nucleating agent as monomers and base chain polymerization, thereby significantly improving the UV resistance and high temperature resistance and mechanical strength of the material. At the same time, after the flame retardant nucleating agent is modified by the nucleating agent and the flame retardant, the flame retardant nucleating agent improves the flame retardant performance of the material and generates a composite polypropylene material with β crystal arrangement during the melt extrusion of the composite polypropylene material, thereby significantly enhancing the high temperature resistance and tensile strength of the composite polypropylene material.

[0057] 2. In the process of preparing modified carbon balls of the present invention, pyrrole is polymerized on the surface of iron oxide to obtain a carbon package structure, and a stable carbon layer structure is obtained by high-temperature calcination and carbonization. The carbon layer is oxidized by a strong oxidation structure formed by concentrated sulfuric acid and hypochlorous acid while removing the template. The iron oxide structure that has not been removed in the early stage of oxidation supports the carbon ball structure. As the oxidation and removal of the iron oxide structure proceed, the active functional groups on the surface of the carbon layer continuously undergo self-polymerization reactions, thereby stabilizing the hollow carbon ball structure. The modified carbon balls obtained after surface modification are dispersed in the composite polypropylene material. While reducing the material density and reducing the vehicle's own weight, the hollow structure isolates heat transfer, thereby significantly improving the high temperature resistance of the material. During the combustion process, it cooperates with the flame retardant nucleating agent to improve the flame retardant performance of the material, and cooperates with the anti-ultraviolet groups on the modified polypropylene chain segments to significantly improve the anti-ultraviolet performance of the material.

[0058] 3. In the process of preparing the flame retardant nucleating agent, the flame retardant ammonium polyphosphate is firstly coated with triethyl orthosilicate, thereby reducing the negative effect of the flame retardant on the mechanical properties of the composite polypropylene material, and by modifying the β-nucleating agent and the double-bond triazine structure on its surface, the composite polypropylene material is used as a heterogeneous nucleation center during the melt extrusion process, so that the composite polypropylene forms a β-crystal with stronger mechanical strength and more uniform molecular chain arrangement. Since the β-crystal structure can be more evenly decomposed and rearranged when heated, it cooperates with the modified carbon ball to improve the high temperature resistance of the material. When the ammonium polyphosphate wrapped by the silicon structure is burned, the flame retardant is slowly released due to the gradual damage of the silicon structure, so that the flame retardant acts more fully, and the acidic structure generated by its decomposition can promote the rapid carbonization of the triazine ring modified on the outside of the silicon structure, and cooperate with the high temperature resistant silicon structure to achieve the effect of assisting flame retardancy, and the surface-modified silicon structure has a higher compatibility with the siloxane structure in the polypropylene segment, thereby reducing the influence of ammonium polyphosphate on the mechanical properties of the material, thereby significantly improving the flame retardant performance and mechanical strength of the material. DETAILED DESCRIPTION

[0059] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0060] The nano iron oxide particles used in the present invention were purchased from Bohuasi Nanotechnology Co., Ltd., with the product number brofos-Fe2O3-50nm;

[0061] The ammonium polyphosphate used in the present invention is purchased from Zhejiang Xusen Flame Retardant Co., Ltd., with the product number of XS-APPII-040.

[0062] Example 1

[0063] This embodiment provides a method for preparing modified carbon spheres for wear-resistant and high-temperature-resistant composite polypropylene materials for automobile decoration, comprising the following steps:

[0064] A1. Preparation of Carbon-coated Iron Oxide

[0065] Weigh: 4.0 g of ammonium persulfate and 100.0 mL of deionized water to prepare a catalyst solution;

[0066] Weigh: 24.0g nano iron oxide particles, 25.0mL pyrrole and 300.0mL deionized water are added to the reactor at a stirring rate of 80rpm. After stirring at room temperature for 10min, 100.0mL of catalyst liquid is added dropwise to the reactor and stirring is continued for 4h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the material is transferred to a drying oven at a temperature of 80°C and vacuum dried to constant weight. Then, the material is transferred to a tubular furnace, and after nitrogen protection is introduced, the temperature is increased to 600°C at a heating rate of 3°C / min, and calcined at a constant temperature for 4h to obtain carbon-encapsulated iron oxide.

[0067] A2. Preparation of hollow carbon spheres

[0068] Weigh: 54.0g carbon-encapsulated iron oxide and 300.0g98.0wt% sulfuric acid are added to a reactor at a temperature of 3°C and stirred at a stirring rate of 80rpm. After keeping warm and stirring for 10 minutes, 36.0g sodium chlorate is added to the reactor. The temperature of the reactor is maintained at 0°C for 2 hours. A saturated sodium hydroxide solution is used to adjust the pH of the reaction system to 7. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the material is transferred to a drying oven at a temperature of 60°C and vacuum dried until the material has a constant weight to obtain hollow carbon spheres.

[0069] A3. Preparation of modified carbon spheres

[0070] Weigh: 84.0g hollow carbon spheres, 24.0g 3-(methacryloyloxy)propyltrimethoxysilane, 8.0g sodium hydroxide and 360.0mL deionized water and add them into the reactor, the temperature of the reactor is raised to 30°C and kept warm for 3h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and after washing 3 times with anhydrous ethanol and deionized water, the material is transferred to a drying oven at 60°C and vacuum dried until the material has a constant weight to obtain modified carbon spheres.

[0071] Example 2

[0072] This embodiment provides a method for preparing modified carbon spheres for wear-resistant and high-temperature-resistant composite polypropylene materials for automobile decoration, comprising the following steps:

[0073] A1. Preparation of Carbon-coated Iron Oxide

[0074] Weigh: 5.0 g of ammonium persulfate and 120.0 mL of deionized water to prepare a catalyst solution;

[0075] Weigh: 36.0g nano iron oxide particles, 30.0mL pyrrole and 300.0mL deionized water are added to the reactor at a stirring rate of 120rpm. After stirring at room temperature for 15min, 120.0mL of catalyst liquid is added dropwise to the reactor and stirring is continued for 6h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the material is transferred to a drying oven at a temperature of 80°C and vacuum dried to constant weight. Then, the material is transferred to a tubular furnace, nitrogen is introduced for protection, and the temperature is increased to 800°C at a heating rate of 5°C / min, and calcined at a constant temperature for 6h to obtain carbon-encapsulated iron oxide.

[0076] A2. Preparation of hollow carbon spheres

[0077] Weigh: 64.0g carbon-encapsulated iron oxide and 360.0g98.0wt% sulfuric acid are added to a reactor at a temperature of 0°C and stirred at a stirring rate of 120rpm. After keeping warm and stirring for 15 minutes, 42.0g sodium chlorate is added to the reactor. The temperature of the reactor is maintained at 0°C for 4 hours. A saturated sodium hydroxide solution is used to adjust the pH of the reaction system to 7. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the material is transferred to a drying oven at a temperature of 60°C and vacuum dried until the material has a constant weight to obtain hollow carbon spheres.

[0078] A3. Preparation of modified carbon spheres

[0079] Weigh: 96.0g hollow carbon spheres, 28.0g 3-(methacryloyloxy)propyltrimethoxysilane, 10.0g sodium hydroxide and 420.0mL deionized water and add them into the reactor, the temperature of the reactor is raised to 50°C and kept warm for 5h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and after washing 5 times with anhydrous ethanol and deionized water, the material is transferred to a drying oven at 60°C and vacuum dried until the material has a constant weight to obtain modified carbon spheres.

[0080] Example 3

[0081] This embodiment provides a method for preparing modified carbon spheres for wear-resistant and high-temperature-resistant composite polypropylene materials for automobile decoration, comprising the following steps:

[0082] A1. Preparation of Carbon-coated Iron Oxide

[0083] Weigh: 4.5 g of ammonium persulfate and 108.0 mL of deionized water to prepare a catalyst solution;

[0084] Weigh: 32.0g nano iron oxide particles, 30.0mL pyrrole and 360.0mL deionized water are added to the reactor at a stirring rate of 120rpm. After stirring at room temperature for 15min, 120.0mL of catalyst liquid is added dropwise to the reactor and stirring is continued for 6h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the material is transferred to a drying oven at a temperature of 80°C and vacuum dried to constant weight. Then, the material is transferred to a tubular furnace, and after nitrogen protection is introduced, the temperature is increased to 700°C at a heating rate of 4°C / min, and calcined at a constant temperature for 5h to obtain carbon-encapsulated iron oxide.

[0085] A2. Preparation of hollow carbon spheres

[0086] Weigh: 72.0g carbon-encapsulated iron oxide and 32.0g98.0wt% sulfuric acid are added to a reactor at a temperature of 3°C and stirred at a stirring rate of 100rpm. After keeping warm and stirring for 15 minutes, 36.0g sodium chlorate is added to the reactor. The temperature of the reactor is maintained at 3°C ​​for 4 hours. A saturated sodium hydroxide solution is used to adjust the pH of the reaction system to 7. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the material is transferred to a drying oven at a temperature of 60°C and vacuum dried until the material has a constant weight to obtain hollow carbon spheres.

[0087] A3. Preparation of modified carbon spheres

[0088] Weigh: 84.0g hollow carbon spheres, 28.0g 3-(methacryloyloxy)propyltrimethoxysilane, 9.0g sodium hydroxide and 360.0mL deionized water and add them into the reactor, the temperature of the reactor is raised to 40°C and kept warm for 4 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and after washing 4 times with anhydrous ethanol and deionized water, the material is transferred to a drying oven at 60°C and vacuum dried until the material has a constant weight to obtain modified carbon spheres.

[0089] Example 4

[0090] This embodiment provides a method for preparing a flame retardant nucleating agent for a wear-resistant and high temperature-resistant composite polypropylene material for automobile decoration, comprising the following steps:

[0091] B1. Preparation of flame retardant

[0092] Weigh: 240.0mL deionized water and 72.0mL ethanol are added to the reactor, the stirring rate is 100rpm, the temperature of the reactor is raised to 40°C, and after stirring for 10 minutes, 48.0g ammonium polyphosphate, 1.2g nonylphenol polyoxyethylene ether and 150.0mL15wt% ammonia water are added to the reactor. After stirring for 20 minutes, 100.0g triethyl orthosilicate is added dropwise to the reactor, and stirred for 2 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and after washing 3 times with anhydrous ethanol and deionized water, the material is transferred to a drying oven at a temperature of 60°C and vacuum dried until the material has a constant weight to obtain a flame retardant.

[0093] B2. Preparation of modified nucleating agent

[0094] Weigh: 42.0g flame retardant, 8.4g 2,2'-methylene-bis(4,6-di-tert-butylphenyl phosphate) basic aluminum, 3.6g sodium hydroxide and 240.0mL N,N-dimethylformamide and add into the reactor, raise the temperature of the reactor to 120°C, keep warm for 30 minutes, after the reaction is completed, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash it 4 times with anhydrous ethanol and deionized water, transfer the material to a drying oven at 60°C and vacuum dry it until the material has a constant weight to obtain a modified nucleating agent.

[0095] B3. Preparation of flame retardant nucleating agent

[0096] Weigh: 32.0g modified nucleating agent, 3.2g 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 3.2mL saturated sodium hydroxide solution and 240.0mL N,N-dimethylformamide and add them into the reactor, the temperature of the reactor is raised to 40°C, and the reaction is kept warm for 20 minutes. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the material is washed three times with anhydrous ethanol and deionized water, and then transferred to a drying oven at a temperature of 60°C and vacuum dried until the material has a constant weight to obtain a flame retardant nucleating agent.

[0097] Example 5

[0098] This embodiment provides a method for preparing a flame retardant nucleating agent for a wear-resistant and high temperature-resistant composite polypropylene material for automobile decoration, comprising the following steps:

[0099] B1. Preparation of flame retardant

[0100] Weigh: 250.0mL deionized water and 84.0mL ethanol are added to the reactor, the stirring rate is 120rpm, the temperature of the reactor is raised to 50°C, and after stirring for 15 minutes, 42.0g ammonium polyphosphate, 2.4g nonylphenol polyoxyethylene ether and 160.0mL 20wt% ammonia water are added to the reactor. After stirring for 30 minutes, 108.0g triethyl orthosilicate is added dropwise to the reactor, and stirred for 3 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and after washing 5 times with anhydrous ethanol and deionized water, the material is transferred to a drying oven at a temperature of 60°C and vacuum dried until the material has a constant weight to obtain a flame retardant.

[0101] B2. Preparation of modified nucleating agent

[0102] Weigh: 48.0g flame retardant, 10.0g 2,2'-methylene-bis(4,6-di-tert-butylphenyl phosphate) basic aluminum, 4.0g sodium hydroxide and 200.0mL N,N-dimethylformamide and add into the reactor, raise the temperature of the reactor to 130°C, keep warm and react for 40min. After the reaction is completed, lower the temperature of the reactor to room temperature, filter the reaction liquid and collect the filter cake, wash it 4 times with anhydrous ethanol and deionized water, transfer the material to a drying oven at 60°C and vacuum dry it until the material has a constant weight to obtain a modified nucleating agent.

[0103] B3. Preparation of flame retardant nucleating agent

[0104] Weigh: 50.0g modified nucleating agent, 4.8g 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 3.6mL saturated sodium hydroxide solution and 240.0mL N,N-dimethylformamide and add them into the reactor, the temperature of the reactor is raised to 60°C, and the reaction is kept warm for 30 minutes. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and after washing 4 times with anhydrous ethanol and deionized water, the material is transferred to a drying oven at a temperature of 60°C and vacuum dried until the material has a constant weight to obtain a flame retardant nucleating agent.

[0105] Example 6

[0106] This embodiment provides a method for preparing a flame retardant nucleating agent for a wear-resistant and high temperature-resistant composite polypropylene material for automobile decoration, comprising the following steps:

[0107] B1. Preparation of flame retardant

[0108] Weigh: 240.0mL deionized water and 8.4mL ethanol are added to the reactor, the stirring rate is 110rpm, the temperature of the reactor is raised to 50°C, and after stirring for 15 minutes, 54.0g ammonium polyphosphate, 2.4g nonylphenol polyoxyethylene ether and 180.0mL18wt% ammonia water are added to the reactor. After stirring for 30 minutes, 120.0g triethyl orthosilicate is added dropwise to the reactor, and stirred for 2 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and after washing 4 times with anhydrous ethanol and deionized water, the material is transferred to a drying oven at a temperature of 60°C and vacuum dried until the material has a constant weight to obtain a flame retardant.

[0109] B2. Preparation of modified nucleating agent

[0110] Weigh: 50.0g flame retardant, 10.0g 2,2'-methylene-bis(4,6-di-tert-butylphenyl phosphate) basic aluminum, 4.8g sodium hydroxide and 240.0mL N,N-dimethylformamide and add into the reactor, raise the temperature of the reactor to 120°C, keep warm for 40min, after the reaction is completed, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash it 4 times with anhydrous ethanol and deionized water, transfer the material to a drying oven at 60°C and vacuum dry it until the material has a constant weight to obtain a modified nucleating agent.

[0111] B3. Preparation of flame retardant nucleating agent

[0112] Weigh: 42.0g of modified nucleating agent, 4.8g of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 3.6mL of saturated sodium hydroxide solution and 240.0mL of N,N-dimethylformamide and add them into the reactor, the temperature of the reactor is raised to 60°C, and the reaction is kept warm for 30 minutes. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and after washing 5 times with anhydrous ethanol and deionized water, the material is transferred to a drying oven at a temperature of 60°C and vacuum dried until the material has a constant weight to obtain a flame retardant nucleating agent.

[0113] Example 7

[0114] This embodiment provides a method for preparing a wear-resistant and high-temperature resistant composite polypropylene material for automobile decoration, comprising the following steps:

[0115] S1. Preparation of modified polypropylene matrix

[0116] Weigh: 84.0 g of the modified carbon spheres prepared in Example 1 and 16.0 g of azobisisobutyronitrile are placed in a reaction kettle and stirred at a stirring rate of 80 rpm for 10 min at room temperature to obtain a prepolymer mixture;

[0117] 1.0 g of the prepolymer mixture was weighed and placed in a high-pressure reactor. The temperature and pressure of the high-pressure reactor were increased to 200° C. and 15 MPa, and 40.0 g of propylene was introduced. The polymerization was carried out at constant temperature and pressure for 40 minutes to obtain a modified polypropylene matrix.

[0118] S2. Preparation of modified polypropylene

[0119] Weigh: 16.0 g of 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol, 24.0 g of 1-allyl-3,5-di[3-(trimethoxysilyl)propyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and 100.0 g of dichlorobenzene to prepare a polymerization solution;

[0120] Weigh: 84.0g of modified polypropylene matrix, 150.0g of polymerization liquid and 400.0mL of dichlorobenzene are added to the reactor, the temperature of the reactor is raised to 150°C, and after stirring for 10 minutes, 10.0g of azobisisobutyronitrile is added to the reactor, and the reaction is kept warm for 1 hour. After the reaction is completed, the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 100°C, and distilled under reduced pressure until no liquid is produced to obtain modified polypropylene.

[0121] S3. Preparation of composite polypropylene

[0122] Weigh: 84.0g modified polypropylene, 18.0g flame retardant nucleating agent prepared in Example 4, 3.6g triphenyl phosphite, 3.6g dibutyltin dilaurate and 2.4g 2-hydroxy-4-octyloxybenzophenone and add them into a twin-screw extruder, the temperatures of the seven temperature sections of the twin-screw extruder from the feed port toward the discharge port are 200°C, 200°C, 205°C, 215°C, 215°C, 220°C, 220°C, the main engine speed of the twin-screw extruder is 80rpm, the pressure is 100bar, and the composite polypropylene is obtained by melt extrusion.

[0123] Example 8

[0124] This embodiment provides a method for preparing a wear-resistant and high-temperature resistant composite polypropylene material for automobile decoration, comprising the following steps:

[0125] S1. Preparation of modified polypropylene matrix

[0126] Weigh: 96.0 g of the modified carbon spheres prepared in Example 2 and 16.0 g of azobisisobutyronitrile are placed in a reaction kettle and stirred at a stirring rate of 80 rpm for 15 min at room temperature to obtain a prepolymer mixture;

[0127] 10.0 g of the prepolymer mixture was weighed and placed in a high-pressure reactor. The temperature and pressure of the high-pressure reactor were increased to 250° C. and 20 MPa, and 42.0 g of propylene was introduced. The polymerization was carried out at constant temperature and pressure for 60 min to obtain a modified polypropylene matrix.

[0128] S2. Preparation of modified polypropylene

[0129] Weigh: 16.0 g of 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol, 28.0 g of 1-allyl-3,5-di[3-(trimethoxysilyl)propyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and 120.0 g of dichlorobenzene to prepare a polymerization solution;

[0130] Weigh: 96.0g modified polypropylene matrix, 145.0g polymerization liquid and 450.0mL dichlorobenzene are added to the reactor, the temperature of the reactor is raised to 160°C, and after stirring for 15 minutes, 12.0g azobisisobutyronitrile is added to the reactor, and the reaction is kept warm for 2 hours. After the reaction is completed, the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 120.0°C, and distilled under reduced pressure until no liquid is produced to obtain modified polypropylene.

[0131] S3. Preparation of composite polypropylene

[0132] Weigh: 96.0g modified polypropylene, 16.0g flame retardant nucleating agent prepared in Example 5, 4.8g triphenyl phosphite, 4.8g dibutyltin dilaurate and 4.8g 2-hydroxy-4-octyloxybenzophenone and add them into a twin-screw extruder, the temperatures of the seven temperature sections of the twin-screw extruder from the feed port toward the discharge port are 200°C, 200°C, 205°C, 215°C, 215°C, 220°C, 220°C, the main engine speed of the twin-screw extruder is 120rpm, the pressure is 150bar, and the composite polypropylene is obtained by melt extrusion.

[0133] Example 9

[0134] This embodiment provides a method for preparing a wear-resistant and high-temperature resistant composite polypropylene material for automobile decoration, comprising the following steps:

[0135] S1. Preparation of modified polypropylene matrix

[0136] Weigh: 95.0 g of modified carbon spheres prepared in Example 3 and 16.0 g of azobisisobutyronitrile are placed in a reaction kettle and stirred at a stirring rate of 100 rpm for 12 min at room temperature to obtain a prepolymer mixture;

[0137] 10.0 g of the prepolymer mixture was weighed and placed in a high-pressure reactor. The temperature of the high-pressure reactor was increased to 240° C., the pressure was increased to 18 MPa, 42.0 g of propylene was introduced, and polymerization was carried out at constant temperature and pressure for 60 minutes to obtain a modified polypropylene matrix.

[0138] S2. Preparation of modified polypropylene

[0139] Weigh: 16.0 g of 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol, 28.0 g of 1-allyl-3,5-di[3-(trimethoxysilyl)propyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and 120.0 g of dichlorobenzene to prepare a polymerization solution;

[0140] Weigh: 80.0g of modified polypropylene matrix, 12.0g of polymerization liquid and 450.0mL of dichlorobenzene are added to the reactor, the temperature of the reactor is raised to 150°C, and after stirring for 15 minutes, 10.0g of azobisisobutyronitrile is added to the reactor, and the reaction is kept warm for 2 hours. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 120°C, and distilled under reduced pressure until no liquid is produced to obtain modified polypropylene.

[0141] S3. Preparation of composite polypropylene

[0142] Weigh: 88.0g modified polypropylene, 18.0g flame retardant nucleating agent prepared in Example 6, 4.2g triphenyl phosphite, 4.2g dibutyltin dilaurate and 4.2g 2-hydroxy-4-octyloxybenzophenone and add them into a twin-screw extruder, the temperatures of the seven temperature sections of the twin-screw extruder from the feed port toward the discharge port are 200°C, 200°C, 205°C, 215°C, 215°C, 220°C, 220°C, the main engine speed of the twin-screw extruder is 100rpm, the pressure is 125bar, and the composite polypropylene is obtained by melt extrusion.

[0143] Comparative Example 1

[0144] The difference between this comparative example and Example 9 is that, when preparing the modified carbon spheres used, in step A2, the use of the drug sodium chlorate is cancelled, and step A3 is cancelled, and hollow carbon spheres are used to replace the modified carbon spheres in an equal amount, and in step S2, polyacrylic acid is used to replace 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol in an equal amount.

[0145] Comparative Example 2

[0146] The difference between this comparative example and Example 9 is that, when preparing the flame retardant nucleating agent used, the use of ammonium polyphosphate is omitted in step B1, and an equal amount of ammonium polyphosphate is added as an auxiliary material into the twin-screw extruder in step S3.

[0147] Comparative Example 3

[0148] The difference between this comparative example and Example 9 is that when preparing the flame retardant nucleating agent used, step B2 is omitted, and in step B3, an equal amount of the flame retardant is used to replace the modified nucleating agent.

[0149] Performance Test:

[0150] The volume abrasion loss of the composite polypropylene prepared in Examples 7-9 and Comparative Examples 1-3 was tested with reference to the standard GB / T 9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrader method)";

[0151] The vertical burning grade of the composite polypropylene prepared in Examples 7-9 and Comparative Examples 1-3 was determined with reference to the standard GB / T 2408-2021 “Horizontal and vertical methods for determination of combustion performance of plastics”;

[0152] The tensile strength of the composite polypropylene prepared in Examples 7-9 and Comparative Examples 1-3 was tested with reference to the standard GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber";

[0153] The density of the composite polypropylene prepared in Examples 7-9 was tested with reference to the standard GB / T 1033.2-2010 "Determination of density of non-foamed plastics Part 2: Density gradient column method", and the specific data are shown in Table 1;

[0154] According to the standard GB / T 7141-2008 "Test Method for Thermal Aging of Plastics", the composite polypropylenes prepared in Examples 7-9 and Comparative Examples 1-3 were placed at a temperature of 90°C for 500 hours of heat preservation treatment, and the tensile strength of the materials was measured according to the standard GB / T528-2009, and the tensile strength retention rate was calculated. The volume abrasion loss of the materials was measured according to the standard GB / T 9867-2008. The specific data are shown in Table 2.

[0155] The composite polypropylene prepared in Examples 7-9 and Comparative Examples 1-3 was subjected to ultraviolet aging tests with reference to standard GB / T 16422.3-2022 "Plastics Laboratory Light Source Exposure Test Method Part 3: Fluorescent Ultraviolet Lamp", the tensile strength of the material was determined with reference to standard GB / T 528-2009, the tensile strength retention rate was calculated, and the volume abrasion of the material was determined with reference to standard GB / T 9867-2008. The specific data are shown in Table 3.

[0156] Table 1 - Performance test data of each sample

[0157]

[0158]

[0159] Table 2-Performance test data of each sample after heat treatment

[0160]

[0161] Table 3 - Performance test data of each sample after UV aging treatment

[0162]

[0163] Data Analysis:

[0164] Comparing and analyzing the data in Tables 1-3 above, the volume loss of the composite polypropylene prepared by the present invention is 29.1 mm 3 , vertical combustion grade is V-0, tensile strength is 88.6MPa and density is 0.6653g·cm -3 After thermal aging, the tensile strength retention rate of the material is 98.6% and the volume wear is 31.2mm 3 After UV radiation aging, the tensile strength retention rate of the material is 98.4% and the volume wear is 33.5mm 3 ;

[0165] Providing the data of Comparative Example 9 and Comparative Example 1, it can be found that the high temperature resistance, UV resistance and mechanical strength of the composite polypropylene prepared in Example 1 are significantly reduced, indicating that compared with the hollow carbon spheres, the modified carbon spheres are uniformly dispersed in the organic system as a cross-linked structure during the synthesis of the modified polypropylene matrix after the double bonds on the surface are modified. In the process of preparing the modified polypropylene, 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol is selected as one of the monomers, and its unique UV-resistant benzotriazole structure and hindered phenol structure are coordinated with the hollow modified carbon spheres to achieve the effect of improving the UV resistance of the material, and the cross-linked structure of the modified carbon spheres and the organic material makes the hollow system inside the material have higher high temperature resistance and mechanical strength;

[0166] By comparing the data of Example 9 and Comparative Example 2, it can be found that the mechanical strength and flame retardant properties of the composite polypropylene prepared in Example 2 are reduced, indicating that the ammonium polyphosphate wrapped by the silicon dioxide structure can achieve a slow release effect of the flame retardant due to the slow damage of the silicon structure during combustion, so that the flame retardant can act more fully, and the acidic structure generated by its decomposition can promote the rapid carbonization of the triazine ring modified on the outside of the silicon structure, and cooperate with the high-temperature resistant silicon structure to achieve the effect of assisting flame retardancy, and the surface-modified silicon structure has a higher compatibility with the siloxane structure in the polypropylene segment, thereby reducing the influence of ammonium polyphosphate on the mechanical properties of the material, thereby significantly improving the flame retardant properties and mechanical strength of the material;

[0167] By comparing the data of Example 9 and Comparative Example 3, it can be found that the wear resistance, tensile strength and high temperature resistance of the composite polypropylene prepared in Example 3 are significantly reduced, indicating that the flame retardant nucleating agent, after lacking the modification of 2,2'-methylene-bis(4,6-di-tert-butylphenyl phosphate) basic aluminum, cannot serve as a heterogeneous nucleation center to promote the composite polypropylene material to form a β-crystal with stronger mechanical strength and more uniform molecular chain arrangement during the melt extrusion process, and because the β-crystal structure can be more evenly decomposed and rearranged when heated, the high temperature resistance of the material is also significantly reduced;

[0168] The present invention prepares modified carbon balls as filling materials, modifies carbon-carbon double bonds on the surface of the modified carbon balls, and uses them as polymerization centers to participate in the preparation of modified polypropylene matrix. The benzotriazole structure and hindered phenol structure with unique UV resistance are selected to coordinate with the hollow modified carbon balls to improve the UV resistance and high temperature resistance of the material and to improve the compatibility of the polypropylene chain segments with the modified carbon balls and the flame retardant nucleating agent as monomers and base chain polymerization, thereby significantly improving the UV resistance and high temperature resistance and mechanical strength of the material. At the same time, after the flame retardant nucleating agent is modified by the nucleating agent and the flame retardant, the flame retardant nucleating agent improves the flame retardant performance of the material and generates a composite polypropylene material with a β-crystal arrangement during the melt extrusion of the composite polypropylene material, thereby significantly enhancing the high temperature resistance and tensile strength of the composite polypropylene material.

[0169] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. Wear-resistant and high-temperature-resistant composite polypropylene material for automobile decoration, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of modified polypropylene, 15-20 parts of flame retardant nucleating agent, 3-5 parts of antioxidant, 3-5 parts of heat stabilizer and 2-5 parts of light stabilizer; Wherein, the preparation method of modified polypropylene comprises the following steps: A1. Using propylene gas as a modifier, the surface of the modified carbon spheres is modified to prepare a modified polypropylene matrix; A2. Add the modified polypropylene matrix, polymer solution and dichlorobenzene into a reactor, raise the temperature of the reactor to 150-160°C, keep warm and stir for 10-15 minutes, add azobisisobutyronitrile into the reactor, keep warm and react for 1-2 hours, and post-treat to obtain modified polypropylene.

2. The wear-resistant and high-temperature-resistant composite polypropylene material for automobile decoration according to claim 1, characterized in that: In step A1, the surface modification operation includes the following steps: B1, placing the modified carbon spheres and azobisisobutyronitrile in a reaction kettle and stirring for 10-15 minutes at room temperature to obtain a prepolymer mixture; B2. The prepolymer mixture is placed in a high-pressure reactor, the temperature of the high-pressure reactor is increased to 200-250° C., the pressure is increased to 15-20 MPa, propylene is introduced, and polymerization is carried out at a constant temperature and pressure for 40-60 minutes to obtain a modified polypropylene matrix.

3. The wear-resistant and high-temperature-resistant composite polypropylene material for automobile decoration according to claim 2, characterized in that: In step B1, the ratio of modified carbon spheres to azobisisobutyronitrile is 8-10 g:1-2 g, and the stirring rate of the reactor is 80-120 rpm; in step B2, the ratio of prepolymer mixture to propylene is 1 g:4-5 g.

4. The wear-resistant and high-temperature-resistant composite polypropylene material for automobile decoration according to claim 1, characterized in that: In step A2, the amount ratio of modified polypropylene matrix, polymerization liquid, dichlorobenzene and azobisisobutyronitrile is 8-10g:10-15g:40-60mL:1.0-1.2g, and the polymerization liquid is prepared from 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol, 1-allyl-3,5-bis[3-(trimethoxysilyl)propyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and dichlorobenzene in a mass ratio of 1-2g:2.4-3.0g:10-15g.

5. The wear-resistant and high-temperature-resistant composite polypropylene material for automobile decoration according to claim 2, characterized in that: The preparation method of modified carbon spheres comprises the following steps: C1. Add nano iron oxide particles, pyrrole and deionized water into a reactor, stir at room temperature for 10-15 minutes, then drop the catalyst into the reactor, continue stirring for 4-6 hours, and perform post-treatment to obtain carbon-encapsulated iron oxide; C2, adding carbon-coated iron oxide and 98.0wt% sulfuric acid to a reactor at a temperature of 0-3°C and stirring, keeping the temperature and stirring for 10-15min, adding sodium chlorate to the reactor, keeping the temperature of the reactor at 0-5°C and reacting for 2-4h, adjusting the pH of the reaction system to 7 with a saturated sodium hydroxide solution, and post-treating to obtain hollow carbon spheres; C3. Add hollow carbon spheres, 3-(methacryloyloxy)propyltrimethoxysilane, sodium hydroxide and deionized water into a reactor, increase the temperature of the reactor to 30-50°C, keep the temperature for 3-5h, and post-treat to obtain modified carbon spheres.

6. The wear-resistant and high-temperature-resistant composite polypropylene material for automobile decoration according to claim 5, characterized in that: In step C1, the stirring rate of the reaction kettle is 80-120rpm, the amount ratio of nano iron oxide particles, pyrrole, deionized water and catalyst liquid is 2-4g:1-3mL:30-40mL:10-15mL, and the catalyst liquid is prepared by ammonium persulfate and deionized water in an amount ratio of 40-50mg:1-1.2mL; in step C2, the stirring rate of the reaction kettle is 80-120rpm, the amount ratio of carbon-coated iron oxide, 98.0wt% sulfuric acid and sodium chlorate is 5-8g:30-40g:3-5g; in step C3, the amount ratio of hollow carbon spheres, 3-(methacryloyloxy)propyltrimethoxysilane, sodium hydroxide and deionized water is 8-10g:2-3g:0.8-1g:30-50mL.

7. The wear-resistant and high-temperature-resistant composite polypropylene material for automobile decoration according to claim 1, characterized in that: The preparation method of the flame retardant nucleating agent comprises the following steps: D1. Deionized water and ethanol are added to a reactor, the temperature of the reactor is raised to 40-50°C, and after being stirred for 10-15 minutes, ammonium polyphosphate, nonylphenol polyoxyethylene ether and 15-20wt% ammonia water are added to the reactor, and after being stirred for 20-30 minutes, triethyl orthosilicate is added dropwise to the reactor, and the mixture is stirred for 2-3 hours, and a flame retardant is obtained by post-processing; D2, adding flame retardant, 2,2'-methylene-bis(4,6-di-tert-butylphenyl phosphate) basic aluminum, sodium hydroxide and N,N-dimethylformamide into a reactor, raising the temperature of the reactor to 120-130°C, keeping the temperature for reaction for 30-40 minutes, and post-treating to obtain a modified nucleating agent; D3. Add modified nucleating agent, 1,3-bis(oxiranylmethyl)-5-(2-propylene)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, saturated sodium hydroxide solution and N,N-dimethylformamide into the reactor, increase the temperature of the reactor to 40-60°C, keep the reaction warm for 20-30 minutes, and post-treat to obtain the flame retardant nucleating agent.

8. The wear-resistant and high-temperature-resistant composite polypropylene material for automobile decoration according to claim 7, characterized in that: In step D1, the stirring rate of the reactor is 100-120rpm, and the amount ratio of deionized water, ethanol, ammonium polyphosphate, nonylphenol polyoxyethylene ether, 15-20wt% ammonia water and triethyl orthosilicate is 20-25mL:6-9mL:4-6g:0.1-0.3g:15-20mL:10-12g; in step D2, flame retardant, 2,2'-methylene-bis(4,6-di-tert-butylphenyl phosphate) basic aluminum, sodium hydroxide and N,N-dimethyl The amount ratio of methylformamide is 3-5g:0.8-1.2g:0.3-0.5g:20-30mL; in step D3, the amount ratio of modified nucleating agent, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, saturated sodium hydroxide solution and N,N-dimethylformamide is 3-5g:0.3-0.5g:0.3-0.5mL:20-30mL.

9. The method for preparing the wear-resistant and high-temperature-resistant composite polypropylene material for automobile decoration according to any one of claims 1 to 8, characterized in that: The modified polypropylene, flame retardant nucleating agent, antioxidant, heat stabilizer and light stabilizer are uniformly mixed and added into a twin-screw extruder for melt extrusion to obtain composite polypropylene.

Citation Information

Patent Citations

  • A kind of high-strength wear-resistant flame-retardant polypropylene and its preparation method

    CN104212061B